Rancang Bangun Panel Surya Berbasis Motor Timer Otomatis Secara Real Time berbasis Arduino Uno - Kadaryono Kadaryono; Mualifi Usman; Riki Abdu Rozak (Jurnal JEETech, 2025)
Electricity is a basic need for almost all Indonesian people. Electricity itself is the main requirement in all economic activities and daily activities, while the availability of fossil fuels for power plants in nature is decreasing, so it requires alternative energy sources that can meet energy needs in the form of solar panels as electricity generators. In this research, a micro-scale solar power generator has been developed for the purpose of lighting the prayer room terrace. In the use of solar panels themselves, it is still static, which results in the utilization of solar energy so far being less than optimal. To optimize solar energy as an electrical energy source, solar panels are an alternative. In this study, the design of a 20WP solar panel uses an automatic timer motor based on the real-time principle, as a driver using a servo motor. From the results of testing the timer motor and without using this timer motor, the voltage produced is different, for those using an automatic timer motor the result is 16.48 Volts, while without using an automatic timer motor the voltage produced is 14.94 Volts and for the efficiency of energy conversion from each method has a different value, namely the value of the satis panel is 48% while the value of the dynamic panel is 52%. So from the results, the highest conversion efficiency was obtained at 52%. The results of the study showed that the greater the conversion efficiency, the greater the voltage produced.